Recent update on potential cytotoxicity, biocompatibility and preventive measures of biomaterials used in dentistry. (9th April 2021) - Bapat, Ranjeet Ajit; Parolia, Abhishek; Chaubal, Tanay; Dharamadhikari, Suyog; Abdulla, Anshad Mohamed; Sakkir, Nasil; Arora, Suraj; Bapat, Prachi; Sindi, Amal M.; Kesharwani, Prashant
Abstract : Dental treatment is provided for a wide variety of oral health problems like dental caries, periodontal diseases, periapical infections, replacement of missing teeth and orthodontic problems. Abstract : Dental treatment is provided for a wide variety of oral health problems like dental caries, periodontal diseases, periapical infections, replacement of missing teeth and orthodontic problems. Various biomaterials, like composite resins, amalgam, glass ionomer cement, acrylic resins, metal alloys, impression materials, bone grafts, membranes, local anaesthetics, etc ., are used for dental applications. The physical and chemical characteristics of these materials influence the outcome of dental treatment. It also impacts on the biological, allergic and toxic potential of biomaterials. With innovations in science and their positive results, there is also a need for awareness about the biological risks of these biomaterials. The aim of dental treatment is to have effective, yet safe, and long-lasting results for the benefit of patients. For this, it is important to have a thorough understanding of biomaterials and their effects on local and systemic health. Materials used in dentistry undergo a series of analyses before their oral applications. To the best of our knowledge, this is the first and original review that discusses the reasons for and studies on the toxicity of commonly used biomaterials for applications in dentistry. It will help clinicians to formulate a methodical approach for the selection of dental biomaterials, thus providing an awareness for forecasting their risk of toxic reactions.